Efek Hukum Perubahan Serta Pembatalan Kontrak; Tinjauan Dari Perspektif Hukum Perikatan - Sianturi, Catherine Rosalina; Gustaf Aria, Muhammad; Choirunnisa, Audi Nayla; Nahriva, Agista Zybilla; S, Surahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Contract amendment and cancellation are crucial issues in the law of ties, especially in the context of maintaining legal certainty and the balance of rights and obligations of the parties involved. This article discusses the legal effects of contract amendment and rescission based on the principles of Indonesian binding law. Based on the Indonesian Civil Code (KUHPer), it examines how modifications to the content of a contract or its unilateral or mutual rescission affect the legal position of the parties. The article also explores the juridical implications of default as a basis for contract cancellation, as well as the role of good faith in contract renegotiation. This research was conducted using a normative approach with a qualitative descriptive analysis method. The results show that contract amendments must be made with the consent of all parties, while rescission can have serious legal consequences, including restitutio in integrum or compensation. This article recommends that contract parties clearly formulate amendment and rescission clauses to avoid future disputes.